Achilles tendon rupture – treatment and complications: A systematic review. Issue 1 (20th March 2014) - Holm, C.; Kjaer, M.; Eliasson, P.
<x xml:space="preserve">Abstract</x> Achilles tendon rupture is a frequent injury with an increasing incidence. Until now, there is no consensus regarding optimal treatment. The aim of this review was to illuminate and summarize randomized controlled trials comparing surgical and non‐surgical treatment of Achilles tendon ruptures during the last 10 years. Seven articles were found and they were all acceptable according to international quality assessment guidelines. Primary outcomes were re‐ruptures, other complications, and functional outcomes. There was no significant difference in re‐ruptures between the two treatments, but a tendency to favoring surgical treatment. Further, one study found an increased risk of soft‐tissue‐related complications after surgery. Patient satisfaction and time to return to work were significantly different in favor of surgery in one study, and there was also better functional outcome after surgery in some studies. These seven studies indicate that surgical patients have a faster rehabilitation. However, the differences between surgical and non‐surgical treatment appear to be subtle and it could mean that rehabilitation is more important, rather than the actual initial treatment. Therefore, further studies will be needed in regard to understanding the interplay between acute surgical or non‐surgical treatment, and the rehabilitation regimen for the overall outcome after Achilles tendon ruptures.